Taxonomic study of the genus Thecobathra Meyrick (Lepidoptera: Yponomeutidae) in China, with descriptions of eight new species - Liu, Haoyu; Wang, Shuxia (Zootaxa, 2023)
Eighteen species of the genus Thecobathra Meyrick, 1922 from China are reviewed. Among them, eight species are described as new to science: T. cuneata Wang, sp. nov., T. magnidentalis Wang, sp. nov., T. meniscata Wang, sp. nov., T. minutiprocessa Wang, sp. nov., T. odontoidea Wang, sp. nov., T. paritetragona Wang, sp. nov., T. pectinacea Wang, sp. nov. and T. setulosa Wang, sp. nov. Also, three species are newly recorded for China: T. acropercna Meyrick, 1922, T. casta (Meyrick, 1907) and T. nakaoi (Moriuti, 1965). The females of T. acrivalvata Fan, Jin et Li, 2008, T. latibasis Fan, Jin et Li, 2008, T. longisaccata Fan, Jin et Li, 2008, T. nakaoi (Moriuti, 1965) and T. paranas Fan, Jin et Li, 2008, and the male of T. microsignata Liu, 1980 are described for the first time in this study. Two synonyms are proposed: T. minuta Sohn, 2018 syn. nov. (= T. albana Liu, 1980), and T. taiwanensis Sohn, 2018 syn. nov. (= T. lambda (Moriuti, 1963). Images of both adults and genitalia of the new species as well as images of genitalia of the newly described male and females are given. A key to the Chinese species is provided, along with a list of all the Thecobathra known species in the world.